Kontribusi Misionaris Pasionis dalam Memajukan Sumber Daya Manusia di Wilayah Kalimantan Barat Ditinjau dari Sejarah Misi: Passionist Missionaries, Human Resources, History - Emanuel, Fransiskus; Pandor, Pius (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
The focus of this research is to present the contribution of the missionaries of the Passionist Congregation in the Nusantara, specifically the West Kalimantan region. The Congregation of Passionists is an institute of consecrated life with papal status in the Roman Catholic Church founded by Saint Paul of the Cross. Missionaries who came to Indonesia came from two provinces, namely Mater Santae Spei from the Netherlands and Pieta from Italy as evangelists in the West Kalimantan region, precisely in Ketapang and Sekadau regencies with an analysis based on the history of the mission. The presence of missionaries in West Kalimantan has made a very extraordinary contribution, related to the development of the faith of the people. The methodology used in this research is a qualitative literary method of documents related to the history of the mission of the Passionist Congregation in Kalimantan. The result to be shown in this study is that the Dayak people in Ketapang and Sekadau Districts in particular were fortunate because of the presence of the Passionist Missionaries where their presence was not only as evangelists but also directly involved in the effort to educate the lives of the Dayaks by establishing schools and scholarship program for children who can afford to go to school.